Ovarian fluid impacts flagellar beating and biomechanical metrics of sperm between alternative reproductive tactics - Butts, Ian A E; Prokopchuk, Galina; Kašpar, Vojtěch; Cosson, Jacky; Pitcher, Trevor E (Journal of experimental biology, 2017)
Alternative reproductive tactics (ARTs) are prevalent in nature, where smaller parasitic males typically have better sperm quality than larger territorial guard males. At present, it is unclear what is causing this phenomenon. Our objective was to gain insights into sperm form and function by examining flagellar beating patterns (beat frequency, wave amplitude, bend length, bend angle, wave velocity) and biomechanical sperm metrics (velocity, hydrodynamic power output, propulsive efficiency) of wild spawning Chinook salmon ARTs. Ovarian fluid and milt were collected to form a series of eight experimental blocks, each composed of ovarian fluid from a unique female and sperm from a unique pair of parasitic jack and guard hooknose males. Sperm from each ART were activated in river water and ovarian fluid. Flagellar parameters were evaluated from recordings using high-speed video microscopy and biomechanical metrics were quantified. We show that ART has an impact on flagellar beating, where jacks had a higher bend length and bend angle than hooknoses. Activation media also impacted the pattern of flagellar parameters, such that beat frequency, wave velocity and bend angle declined, while wave amplitude of flagella increased when ovarian fluid was incorporated into activation media. Furthermore, we found that sperm from jacks swam faster than those from hooknoses and required less hydrodynamic power output to propel themselves in river water and ovarian fluid. Jack sperm were also more efficient at swimming than hooknose sperm, and propulsive efficiency increased when cells were activated in ovarian fluid. The results demonstrate that sperm biomechanics may be driving divergence in competitive reproductive success between ARTs.
Keywords: bičík spermie; biomechanika; Salmon; zvířata; Sperm Motility; ovarium; Ovary; Sperm Tail; mužské pohlaví; Ontario; motilita spermií; Reproduction; rozmnožování; ženské pohlaví; Animals; losos; Male; Biomechanical Phenomena; Female